2004
DOI: 10.1194/jlr.m300447-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of cis-9,trans-11 or trans-10,cis-12 conjugated linoleic acid into plasma and cellular lipids in healthy men

Abstract: Incorporation of cis -9, trans -11 or trans -10, cis -12 conjugated linoleic acid into plasma and cellular lipids in healthy men Abstract This study investigated the incorporation of cis -9, trans -11 conjugated linoleic acid (c9,t11 CLA) and trans -10, cis -12-CLA (t10,c12 CLA) into plasma and peripheral blood mononuclear cell (PBMC) lipids when consumed as supplements highly enriched in these isomers. Healthy men (n ‫؍‬ 49, age 31 ؎ 8 years) consumed one, two, and four capsules containing ‫ف‬ 600 mg of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 47 publications
10
41
0
Order By: Relevance
“…These minimal detection levels are similar to that published by other groups (Mougios et al, 2001). In addition, the level of t10,c12-CLA enrichment was very variable between subjects whereby the standard deviation was almost equal to the mean values as has been demonstrated in a recent publication (Burdge et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
“…These minimal detection levels are similar to that published by other groups (Mougios et al, 2001). In addition, the level of t10,c12-CLA enrichment was very variable between subjects whereby the standard deviation was almost equal to the mean values as has been demonstrated in a recent publication (Burdge et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
“…Although several groups have reported that c9,t11-CLA is metabolized in cells and incorporated into plasma and tissue lipids ( 15,28 ), only a few studies investigated its effects on cellular lipids. Metabolism of t9,t11 -CLA and its contribution to cellular lipids is completely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning CLA metabolism, it has been shown that c9,t11 -CLA incorporates into phospholipids of leukemia cells and can be found in plasma and cellular lipids of healthy men supplemented with a diet enriched with this CLA isomer ( 14,15 ). However, so far the effects of c9,t11 -CLA on individual phospholipid classes, phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS), and its cellular distribution are not precisely described, and data on the metabolism of the t9,t11 -CLA isomer are completely unavailable.…”
mentioning
confidence: 99%
“…273 respectively; P < 0 . 0005) when consumed in the diet (Burdge et al 2004). No evidence was found for differential incorporation of these isomers into PBMC, although the final concentration of each isomer was reported to be markedly lower than that in plasma phosphatidylcholine and cholesteryl ester fractions at each dose (Burdge et al 2004).…”
Section: Conjugated Linoleic Acid and Immune Functionmentioning
confidence: 98%